The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/f12070823
|View full text |Cite
|
Sign up to set email alerts
|

Biotic and Abiotic Determinants of Soil Organic Matter Stock and Fine Root Biomass in Mountain Area Temperate Forests—Examples from Cambisols under European Beech, Norway Spruce, and Silver Fir (Carpathians, Central Europe)

Abstract: Forest ecosystems significantly contribute to the global organic carbon (OC) pool, exhibiting high spatial heterogeneity in this respect. Some of the components of the OC pool in a forest (woody aboveground biomass (wAGB), coarse root biomass (CRB)) can be relatively easily estimated using readily available data from land observation and forest inventories, while some of the components of the OC pool are very difficult to determine (fine root biomass (FRB) and soil organic matter (SOM) stock). The main objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 113 publications
1
4
0
Order By: Relevance
“…While stands with low total BA always resulted in low stand-level C stocks in tree woody biomass, SOC stocks were independent of total stand BA. The negligible effects of BA on soil C relative to tree woody C across triplet types agree with our hypothesis (H1) and previous studies (Cécillon et al 2017 ; Laganiere et al 2010 ; Ruiz-Peinado et al 2013 ) but contradict others (González et al 2012 ; De Marco et al 2016 ; Zielonka et al 2021 ). Inconsistent results for BA effects on soil C could be because the balance between litter input and decomposition processes governs soil C storage (Liu et al 2018 ; Vesterdal et al 2013 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…While stands with low total BA always resulted in low stand-level C stocks in tree woody biomass, SOC stocks were independent of total stand BA. The negligible effects of BA on soil C relative to tree woody C across triplet types agree with our hypothesis (H1) and previous studies (Cécillon et al 2017 ; Laganiere et al 2010 ; Ruiz-Peinado et al 2013 ) but contradict others (González et al 2012 ; De Marco et al 2016 ; Zielonka et al 2021 ). Inconsistent results for BA effects on soil C could be because the balance between litter input and decomposition processes governs soil C storage (Liu et al 2018 ; Vesterdal et al 2013 ).…”
Section: Discussionsupporting
confidence: 92%
“…Stand density is another key factor that influence C accumulation in both aboveground woody biomass and coarse root biomass (Torres and Lovett 2013 ), and in the soil (Laganiere et al 2010 ; Zielonka et al 2021 ). Among silvicultural treatments, Ruiz-Peinado et al ( 2013 ) considers activities that alter stand density (such as regeneration felling and thinning) as those with the greatest impact on stand biomass and consequently the amount of C in the forest.…”
Section: Introductionmentioning
confidence: 99%
“…This is the case of calcic eutric cambisol, which has a higher presence in one of the causes of spreading valuable stands in this region [72]. On the other hand, lithic soils are not favourable for silver fir due to its taproot system [34,73,74]. In this contest, silver fir stands from the Southern Carpathians have lower productivities.…”
Section: The Soilmentioning
confidence: 99%
“…When mixed, spruce root biomass did not differ from the pure spruce stand, whereas the presence of beech in mixtures showed a significantly higher specific root length and specific surface area of fine roots compared to pure beech stands (Bolte and Villanueva 2006). In the Western Carpathians, Zielonka et al (2021) found the highest levels of fine-root biomass below silver fir compared to Norway spruce and European beech. Despite the fact that beech stores less carbon in soil compared to maple and Communicated by Agustin Merino.…”
Section: Introductionmentioning
confidence: 84%
“…Spruce is a main Central European commercial species, whereas the most important conifer of the past-fir is very limited. These three trees accompany each other in different mixtures along a gradient from foothills to Alpine sites in Europe (Hilmers et al 2020;Filipiak et al 2021;Zielonka et al 2021). As European foresters are facing a decline of monocultures, the issue of mixed-species forest restoration has been raised.…”
Section: Introductionmentioning
confidence: 99%